Comparing the Frequency of Lymphoceles Which Needed Intervention in Recipients of Living Donor Versus Deceased Donor Kidney Transplants - Simforoosh, Nasser; Basiri, Abbas; Tabibi, Ali; Marufi, Hamed; Kashi, Amir Hossein (Urology Journal, 2022)
Objective: In this study, we aimed to compare the frequency of lymphoceles that needed intervention in recipients who received kidneys from living versus deceased donors. Materials and methods: The records of all patients who underwent kidney transplantation at the Labbafinejad Hospital from 2012 to 2021 were retrospectively reviewed to determine the incidence of lymphoceles that needed intervention for management. Results: From March 2012 to April 2021, 1752 patients received kidney transplantation in Labbafinejad Hospital including 975 transplantations from living donors and 777 transplantations from deceased donors. Symptomatic lymphoceles were observed postoperatively in 23 patients. Symptoms included compressive effect on the ureter, hydroureteronephrosis of the transplanted kidney, frequency, urinary retention, infection, abdominal discomfort, or rise in serum creatinine. Out of 23 patients who needed intervention for symptomatic lymphocele, 15 patients were recipients of living donors and 8 patients were recipients of deceased donors [1.53% versus 1.03%, P=.40]. Intervention consisted of open surgical drainage in 6 patients [4 recipients of living donors and 2 recipients of deceased donors], and nephrostomy insertion in 17 patients. Open operation was necessary in 5 (47%) patients in whom arterial anastomosis was made to the internal iliac artery versus 1 (9%) patient in whom the anastomosis was not made to the internal iliac artery (P=0.15). Conclusion: Symptomatic lymphoceles which needed intervention were observed in low frequency (1.31%). Most cases can be managed by endoscopic drainage without relapse. Type of donation had no relationship with the need for open or endoscopic intervention in lymphoceles. A higher proportion of open surgeries to control lymphocele were observed in recipients in whom the internal iliac artery was used for arterial anastomosis however the difference was not statistically significant.